Advancing Lumbar Surgery: Exploring the Efficacy and Outcomes of Spinal Anesthesia in 41 Cases. - Kalhoro , Aurangzeb; Abdul Sattar M. Hashim (International Journal of Endorsing Health Science Research, 2023)
Background: Spinal anesthesia has emerged as a safe and effective alternative for patients with lumbar spine degenerative disease, particularly those with comorbidities. The aim of this study was to investigate the role of spinal anesthesia in the management of lumbar disc degeneration at the Neurospinal and Cancer Care Institute in Karachi. Methodology: This prospective cohort study was conducted at the Neurospinal and Cancer Care Institute's Department of Neurosurgery. The study included patients with a mean age of 53.43 ± 8.11 years and was carried out from February 2019 to August 2022, following approval from the Institutional Review Board. Results: The study comprised predominantly high-risk patients, with 32 individuals (78%) having associated comorbidities. The American Society of Anesthesiologists (ASA) classification was used to assess the patients' risk level, with 3 patients (7.31%) classified as ASA grade I, 21 patients (51.21%) as ASA grade II, 16 patients (39.02%) as ASA grade III, and 2 patients (4.87%) as ASA grade IV. The most commonly affected level of disc degeneration was L4-L5 (63.41%), followed by L5-S1 (36.58%), with the majority of stenosis occurring at L4-S1. No complications such as urinary retention, vomiting, or dural tear were observed. Pain relief was assessed using the visual analogue scale (VAS), with 23 patients having a preoperative VAS score of 7, 14 patients with a score of 8, and 4 patients with a score of 9. Postoperatively, 18 patients (43.9%) had a VAS score of 2, 23 patients (56%) had a score of 1, and 5 patients (12%) had a score of 0. Conclusion: Based on the findings of this study, spinal anesthesia can be considered a suitable alternative to general anesthesia for patients with comorbidities or those classified as ASA grade I/II. This technique offers several advantages, including cost-effectiveness, shorter anesthesia duration, and fewer complications. These findings support the use of spinal anesthesia in patients with limited spinal pathology in the lumbar spine.